'Marriage of incommensurables': a geometric conversation between an artist and a mathematician. Issue 3 (8th October 2019) - Reynolds, Mark A.; Wassell, Stephen R.
ABSTRACT: The artist Mark Reynolds is interviewed by the mathematician Steve Wassell in order to explore Reynolds' approach to mathematics in his art. Reynolds' Square Root Phi Series, which spans over a decade, is used as an example of his artwork, helping to highlight his unique style. The concept of 'marriage of incommensurables' is discussed, as well as exact versus approximate geometric constructions. GRAPHICAL ABSTRACT: